Drinking in Iceland and Ideas of the North - Ólafsdóttir, Hildigunnur (Presses de l'Université du Québec, 2011)
It is hypothesized that ideas about the North as an extreme and turbulent force have been instrumental in shaping images relating to Icelanders’ drinking culture and the imagined position of alcohol in the community. In line with this understanding, the governing image of the position of alcohol in society has been of an excessive drinking pattern that is based on a special connection between alcohol and the national character. The objective of this study is to examine how specific preconceptions about the North have been linked to images of the drinking culture and to define emphases and conflicts surrounding these assumptions. Particular attention is paid to the image of the drinking pattern as it is represented abroad and how the image of the Icelandic drinking pattern is used in alcotourism. The sources used for this study are various types of written materials, newspapers, and advertisements, particularly from the last two decades. The method is analysis of text and discourse. The conclusions reveal that the image of Icelandic drinking culture is deeply rooted and has been instrumental in shaping the position on alcohol, although this does not preclude that the image is challenged. The image of drinking has an intrinsic value as it is used both to reject an old pattern and to justify a new one, yet images appear to have had little value as a tool for class distinction. On the other hand, preconceptions acquire practical value when used in promoting tourism.